APLIKASI MATRIKS HANKEL PADA PERHITUNGAN RESULTAN DUA POLINOMIAL - Rosnawati, Mrs R. (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2002)
Let F be a field, f and g in F[x], with degre f is n and degre g is m. Computing resultant two polynomials with Hankel matrics give a size of matrics less than Sylvester method, that is maximum n or m.Keyword : resultan, Hankel matrics, Sylvester method